L'applicabilité de la méthode hydrogéomorphologique au domaine aride du Xinjiang (Chine) : le cas du bassin versant du Karakash - Maihepireti Wulamu; Jean-Louis Ballais; Virginie Delorme (Physio-Géo)
The Karakash river watershed is situated in an arid zone, in the southern part of Xinjiang. In this watershed, floods occur during summer, almost each year, and destroy crops that are the main income of the population. Flooding cause damages that hinder socio-economical development. Flood prevention must be integrated at the global water management. Our work demonstrates the applicability of hydrogeomorphological method in the Karakash watershed. Hydrogeomorphological mapping provides informations that are able to permit a spatial planning to prevent and reduce flood risks.